The Hidden Costs of Clean Election Reform - Schaffer, Frederic Charles (Book collections on Project MUSE., 2008)
"By understanding how even good-faith efforts to improve corrupt or flawed electoral practices may impede the democratic process, The Hidden Costs of Clean Election Reform suggests new ways to help prevent future breaches of democracy."--Back inside jacket